Hormetic effects of noncoplanar PCB exposed to human lung fibroblast cells (HELF) and possible role of oxidative stress. Issue 12 (18th June 2014) - Hashmi, Muhammad Zaffar; Khan, Kiran Yasmin; Hu, Jinxing; Naveedullah; Su, Xiaomei; Abbas, Ghulam; Yu, Chunna; Shen, Chaofeng
ABSTRACT: Hormesis, a biphasic dose–response phenomenon, which is characterized by stimulation of an end point at a low‐dose and inhibition at a high‐dose. In the present study we used human lungs fibroblast (HELF) cells as a test model to evaluate the role of oxidative stress (OS) in hormetic effects of non coplanar PCB 101. Results from 3‐(4, 5‐dime‐thylthiazol‐2‐yl)‐2, 5‐diphenyltetrazo‐lium bromide (MTT) assay indicated that PCB101 at lower concentrations (10 −5 to 10 −1 μg mL −1 ) stimulated HELF cell proliferation and inhibited at high concentrations (1, 5, 10, and 20 μg mL −1 ) in a dose‐ and time‐dependent manner. Reactive oxygen species (ROS), malondialdehyde (MDA) and superoxide dismutase (SOD) (except 48 h) showed a significant increase at higher concentrations of PCB 101 than those at the lower concentrations with the passage of time. Antioxidant enzymes such as glutathione peroxidase (GSH‐Px) exhibited decreasing trends in dose and time dependent manner. Lipid peroxidation assay resulted in a significant increase ( P  < 0.05) of MDA level in PCB 101‐treated HELF cells compared with controls, suggesting that OS plays a key role in PCB 101‐induced toxicity. Comet assay indicated a significant increase in genotoxicity at higher concentrations of PCB 101 exposure compared to lower concentrations. Overall, we found that HELF cell proliferation was higher at low ROS level and vice versa, which revealed activation of cell signaling‐mediated hormetic mechanisms. The results suggested that PCB 101 has hormetic effects to HELF cells and these were associated with oxidative stress. © 2014 Wiley Periodicals, Inc. Environ Toxicol 30: 1385–1392, 2015.